The analysis of sharia compliance in the implementation of KPR Syariah iB Hebat product at BPRS Dana Amanah Surakarta - Sup, Devid Frastiawan Amir; Firdaus, Muhammad Irkham; Bilhaq, Aqil Mutashim (Universitas Islam Indonesia, 2023)
IntroductionBPRS Dana Amanah Surakarta, as part of a sharia entity, has an obligation to comply with sharia. One of the products implemented is KPR Syariah iB Hebat financing.ObjectivesThis research aims to analyze sharia compliance in the implementation of KPR Syariah iB Hebat products at BPRS Dana Amanah Surakarta, as well as the role of DPS in controlling and supervising every operational activity and product so that it remains in accordance with sharia regulations and principles. MethodThis research used a qualitative approach, in the form of field research, to describe the field data obtained and analyzed in this research.ResultsThe contract used in the KPR Syariah iB Hebat product at BPRS Dana Amanah Surakarta is a murabahah, istishna’ parallel, and musyarakah mutanaqishah contracts, based on DSN-MUI fatwa. The provisions listed in the DSN-MUI fatwa are then compiled into a letter of agreement. DPS supervises the development of new BPRS products and activities and supervises BPRS activities. Until now, there have been no findings of serious deviations from sharia aspects at BPRS Dana Amanah Surakarta, usually the findings are limited to administrative requirements that can be fulfilled. ImplicationsBPRS Dana Amanah Surakarta should maintain the sharia compliance for KPR Syariah iB Hebat and its other financial products. Other Islamic micro financial institutions can follow the steps taken by BPRS Dana Amanah Surakarta to engineer its financial products.Originality/NoveltyThis research made an important contribution in the form of concepts and implementation on sharia compliance, which is a part that should not be separated from the activities of sharia entities, as a reference for analyzing and developing the financial, economic, and Islamic business in the future.